2022
DOI: 10.1007/s10560-022-00844-6
|View full text |Cite
|
Sign up to set email alerts
|

Improving Parenting Competency and Permanency Awareness for Kinship Foster Parents Through In-Service Licensure Training

Abstract: Child welfare jurisdictions increasingly place foster children with kinship foster parents as a means of meeting their need for stability, family connection, and behavioral and emotional support. However, the lack of financial and educational assistance provided to kin by child welfare authorities often undermines these caregivers’ ability to provide effective and lasting care for the children in their homes. This study uses a mixed-methods approach to understand how formal training and licensure processes can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…This article serves as a reminder that passing a policy may create the structure or resources families need, but successful implementation is key to realizing the intended policy objectives, in this instance increased permanency and positive child adjustment associated with licensure. Similar to the article by Gibbs et al, (2022), this study highlighted the challenges caregivers encounter with barriers to participation and the lack of support to manage relational difficulties with birth parents.…”
Section: Training and Parenting Programsmentioning
confidence: 65%
See 2 more Smart Citations
“…This article serves as a reminder that passing a policy may create the structure or resources families need, but successful implementation is key to realizing the intended policy objectives, in this instance increased permanency and positive child adjustment associated with licensure. Similar to the article by Gibbs et al, (2022), this study highlighted the challenges caregivers encounter with barriers to participation and the lack of support to manage relational difficulties with birth parents.…”
Section: Training and Parenting Programsmentioning
confidence: 65%
“…In other words, many interventions or trainings lack relevance to the population or issue at hand. Gibbs et al, (2022) examined the lack of attention to training and support for kinship foster parents, even though kin caregivers are increasingly relied on to provide substitute care for relative children. The participants in this study reported that incomplete and inaccurate communication regarding licensing processes, as well as practical difficulties attending training, irrelevant session content, and stringent licensing requirements acted as barriers to access training.…”
Section: Primary and Secondary Data Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the primary ways kinship caregivers receive financial assistance to provide care for children of relatives is through foster care payments [32]. However, many kinship caregivers cannot benefit from this type of assistance due to foster care licensing requirements [33,34]. Even when these caregivers can receive foster care payments, there is evidence that the payment amounts in all but four states in the U.S. are insufficient when considering the financial demands associated with meeting the needs of children in their care [35].…”
Section: The State Of Kinship Carementioning
confidence: 99%